Multiple urinary bladder calculi: a rare cause of irreducible uterovaginal prolapse - Mohi, Manjit Kaur; Kaur, Manjeet; Kaur, Balwinder; Kaur, Satinder Pal; Aggarwal, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
A case of irreducible prolapse with multiple bladder calculi in a 65-years-old multiparous, postmenopausal woman is reported. Inability to walk, constipation and urinary incontinence were her primary complaints. Routine ultrasound of the abdomen and pelvis failed to reveal multiple vesical calculi as the prolapse was lying outside the pelvis. However, targeted plain X-ray of the prolapsed mass showed multiple vesical calculi. The patient was managed with single-stage vaginal hysterectomy and laparotomy. First vaginal hysterectomy was done then prolapsed cystocele was reduced and extraperitoneal vesicolithotomy done. Currently, the patient is relieved of all symptoms. Management of an irreducible procidentia and a hard mass in the anterior compartment, as in this case, can be challenging and requires a diligent effort to confirm the diagnosis and to execute the appropriate surgical protocol to achieve optimal outcome with minimal intra- and post-operative complications.